THE WAR ON TERROR AND US STRATEGIES AGAINST AL-QAEDA AFTER 9/11 - Fatima Ali Rashid; Rizwan Ali Shah; Ateeqa Tanveer Khan; Zahra Ejaz; Sana Asif (International Journal of Contemporary Issues in Social Sciences, 2023)
In the immediate aftermath of 9/11, the US launched a military campaign in Afghanistan, where Al Qaeda had established its base of operations. This was followed by the invasion of Iraq in 2003, based on the belief that the country possessed weapons of mass destruction and was providing support to terrorist groups. These actions were part of the US strategy of pre-emptive strikes against potential threats, a doctrine that came to be known as the ’Bush Doctrine.’ The US also formed alliances with other countries, such as Pakistan and Saudi Arabia, in an effort to disrupt and dismantle Al Qaeda’s network. Therefore, this paper utilizes a case study approach to gain a nuanced understanding of the specific actions, strategies, and policies employed by the United States in its efforts to dismantle and neutralize Al Qaeda, In addition to military actions, the US also utilized other strategies in the War on Terror. One such strategy was the implementation of enhanced intelligence gathering and surveillance measures, including the controversial Patriot Act. The US also focused on cutting off the financial resources of terrorist organizations, freezing their assets and tracking their financial transactions. Another key aspect of the US strategy was the use of targeted drone strikes to eliminate high-level Al Qaeda leaders. While these strategies have had some success in weakening Al Qaeda, the organization has evolved and adapted, posing new challenges for the US in its ongoing war on terror. This research paper concludes that the War on Terror and the US strategies towards Al Qaeda after 9/11 have had a significant impact on global politics and security. While there have been successes in disrupting and weakening Al Qaeda’s operations, the threat of terrorism continues to loom large. The study recommends that the US, along with its allies, must continue to adapt and evolve its strategies in order to effectively combat this persistent threat. The fight against Al Qaeda and other terrorist organizations remains a critical and ongoing battle in the quest for global peace and security.